2023
DOI: 10.1002/rem.21757
|View full text |Cite
|
Sign up to set email alerts
|

A review on the adsorption of diuron, carbaryl, and alachlor using natural and activated clays

Abstract: Pesticides are considered predominant organic pollutants because they are widespread in many ecosystems. Pesticide residues can degrade chemically, physically, and biochemically in nature, but, because of their high stability and, in some cases, water solubility, they continue to persist in the environment. Pesticides have been eliminated from contaminated waters using a variety of methods that fall under the categories of biological, chemical, physical, and physicochemical remediation processes from various t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…This is in accordance with the study of Singh et al [ 70 ], who found that carbofuran adsorption was strongly correlated with clay content followed by the organic matter content of soils. However, insecticide uptake on the loam soil material was attributed solely to montmorillonite, presumably due to the enhanced physical diffusion of the pesticide into Mt interlayers, governed by van der Waals forces [ 71 ]. It is commonly observed that the particulate organic (or organo-mineral) soil fractions form stable microaggregates where the retention of pesticides could depend more on steric factors and diffusion mechanisms than on the type and amounts of oxygen-containing functional groups [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with the study of Singh et al [ 70 ], who found that carbofuran adsorption was strongly correlated with clay content followed by the organic matter content of soils. However, insecticide uptake on the loam soil material was attributed solely to montmorillonite, presumably due to the enhanced physical diffusion of the pesticide into Mt interlayers, governed by van der Waals forces [ 71 ]. It is commonly observed that the particulate organic (or organo-mineral) soil fractions form stable microaggregates where the retention of pesticides could depend more on steric factors and diffusion mechanisms than on the type and amounts of oxygen-containing functional groups [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lower Qmax values may have been due to the competition between aldrin and the other ions for adsorption sites on the surface, resulting in reduced adsorption of Hg 2+ , Pb 2+ , and Cd 2+ (Figure 3). The dimensionless equilibrium (R L ) parameter was close to unity for most of the binary combinations, indicating a favorable adsorption process [36]. The quaternary combinations showed favorable adsorption with R L values less than one (Table 4).…”
Section: Multi-component (Binary and Quaternary) System Adsorption Of...mentioning
confidence: 88%